Pemberian Aromaterapi Lavender terhadap Peningkatan Kualitas Tidur pada Lansia - Sari, Afifah Dian; Kartinah, Kartinah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effect of lavender aromatherapy on improving sleep quality in older people. The research method used is a pre-experimental design case study with a one-group pre-test - post-test design. The results of the study showed that based on the results of the statistical test, namely the Paired sample t-test, a p-value of 0.004 was obtained, so the P-Value <0.05, which means that there is an effect of lavender aromatherapy on improving sleep quality in older people before and after aromatherapy. In conclusion, lavender aromatherapy significantly affects older people who experience poor sleep quality, as indicated by a significant difference between the values ​​before and after the intervention. Keywords: Aromatherapy, Sleep Quality, Elderly, Lavender